The Art of managing Human Resources as a Human Resource Development Strategy to Increase PT Bhinneka Tekno Sejati Employees’ Creativity - Guslina, Indri (Eduvest - Journal of Universal Studies, 2023)
The study aims to analyze the art of managing Human Resources (HR) as an HR development strategy that can increase employee creativity at PT Bhinneka Tekno Sejati. In the face of the digital era and rapid change, effective and efficient HR management is the key to the company's success. The method used in this study is a qualitative study with data collection techniques through interviews, observations, and documentation studies. The results showed Management by Objective (MBO) improved work performance by directing behavior. These models tend to be fair because standards are expressed in relatively objective terms. This model is also fast, practical, inexpensive, and motivates workers by giving them the opportunity to cooperatively set their own goalsIn the context of PT Bhinneka Tekno Sejati, the art of managing HR has succeeded in increasing employee creativity. This can be seen from the improvement in the quality of products and services, as well as increased customer satisfaction. Therefore, companies need to continue to develop effective and efficient HR management strategies to face future challenges and opportunities.